(3EQTGO GdYbd GdSdje Edi eRGjG GdcJGH GdcQjes - (3eMeO Hf eMeO Hf eUWai GdYeGOj, Gdehdi CHh GdSYhO,J (B982 (3g` s
(3ChdgG (B:s
(3Chdg JaSjQ ShQI jS s
(3BNQgG (B:s
(3BNQg ai JaSjQ ShQI GdfGS (B" (3Ke Hjf HGdLfI hGdfGS , aEf cd aQO ef CaQGO GdaQjbjf eHJdi HfSjGf Mb Gddg JYGdi YUefG Gddg JYGdi ef GdZadI Yf PcQg , hhabfG dCOGA Mbhb TcQg s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdBjGJ ajgG HGdMeQIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B7 - (3U (B59 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B11 - (3U (B301s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ s
Keywords: (3GdJaSjQ hYdhe GdbQBfs